Application of Risk Management Quality Integrated And Impact on the Quality Students Improvement MAN 2 Medan Model - Nur Azizah (International Journal Of Education, Social Studies, And Management (IJESSM), 2021)
Implementation of Total Quality Management of in school has a purpose main give satisfaction to the customer services of education either internal or external to the results of product quality . Implementation of Total Quality Management in schools requires at least three stages of implementation , namely : preparation , planning , and implementation . Problems are contained in the study times this include How the implementation of management quality integrated in Man 2 Model Terrain , How is the impact of the implementation of management quality integrated in the improvement of the quality of the participants didikdi Man 2 Model Medan method of research that is done is to use approach qualitative with technique of collection of data such as observation , interview and documentation . The results of his research is the management quality integrated merupaka a theory of knowledge management who directs the leadership of the organization and its personnel to carry out repairs quality constantly are focused on achieving the satisfaction of customers internal and customers externally. Implementation of the management quality integrated in MAN 2 Model Terrain increasingly in improved based on the needs of customers in order to graduate from madrash that can fulfill the wishes and expectations of the community . The impact of the implementation of management quality terpdusejauh it can be seen from the attitude , behavior behavior , and ways of view of students and residents madrsah lainny to continue melakukn repair and can compete dier digital now this. Constraints that expressed by the head of the madrassa in the improvement of the quality of the participant students in the form of time which is in charge sometimes not in accordance with the conditions and expectations